The Management of Chylous Ascites: Description of a New Technique Regarding a Clinical Case - Hugo Otaola-Arca; Patricio Vargas; Marcelo Orvieto; Carmen Niño-Taravilla; Hugo Bermúdez (New Advances in Medicine and Medical Science Vol. 2, 2023)
Chylous ascites (CA) is a rare postoperative complication that can lead to malnutrition and immunodeficiency. As a result, surgical interventions are reserved for patients who are refractory, and the primary success factor for these interventions is locating the point of leakage, which is frequently difficult. Most CA cases were managed conservatively in the literature, with a minority treated with surgical intervention. We present the case of a 56-year-old man who developed chylous ascites following a laparoscopic radical nephrectomy and lumbo-aortic lymphadenectomy for kidney cancer. At first, the patient was managed with dietary changes and drainage placement. Following that, lipiodol lymphography, percutaneous embolisation of the leakage point, and total parenteral nutrition were established. Ultimately, after identifying the leakage point with methylene blue injection through an inguinal node, the patient underwent laparoscopic repair. The procedure was completed successfully, and no complications were reported. To improve the results of surgical repair of refractory chylous ascites in a subset of patients, intranodal methylene blue injection can be a beneficial technique for pinpointing the source of leakage.